When a Political Party Turns against Its Cadres: ZANU PF Factional Infightings 2004-2017. Issue 2 (3rd April 2019) - Hove, Mediel
ABSTRACT: This article examines how the Zimbabwe African National Union Patriotic Front party turned against its cadres between 2004 and 2017. It argues that the infightings were caused by Mugabe, who pitted one faction against the other as the Zimbabwe African National Union (ZANU) PF cashiered its cadres to safeguard Mugabe. It was the same militarized factionalism that catapulted Mugabe to the helm of the national liberation movement in 1977, spearheaded his removal in 2017, and propelled Mnangagwa to become President. However, Mnangagwa – who replaced Mugabe, the Machiavellian manipulator of his party's factionalism – lacked adroit skills, hence the sense of rudderlessness and incoherence in the party.